Urban Containment Planning: Is It Effective? The Case of Portland, OR - Giulio Giovannoni (MDPI AG, 2021)
The paper attempts to evaluate Oregon’s and Portland’s growth management policies as for their tradeoffs between effectiveness in containing urban sprawl and impacts on housing markets and on property values. Carruthers argued that in order to correctly evaluate growth management policies, it is necessary to jointly consider their effects on urban development patterns, on land and housing markets, and on the fragmentation of land use controls. Nowadays, we have sufficient empirical research to evaluate the effects of Oregon’s growth management policies both on land markets and housing affordability and on urban development patterns. Therefore, the time has come to comprehensively reanalyze this longstanding case of public regulation. Once again, the issue of comparing grounded-on-planning–regulations’ effectiveness with grounded-on-price regulations’ effectiveness is at stake. The paper finds that urban-containment centralized-planning in Portland and Oregon have not been effective in containing sprawl and that price-based mechanisms are the most logical solution to the excess of sprawling urban growth.